FACTORS INFLUENCING ANTENATAL CARE UTILIZATION IN ETHIOPIA: A SYSTEMATIC REVIEW - Gudu, Wondimu (Ethiopian Journal of Reproductive Health, 2018)
ABSTRACT BACKGROUND Maternal death is a major public health problem in Ethiopia. Antenatal care (ANC) utilization is believed to promote the uptake of obstetric care services and hence improve maternal health. But ANC coverage is low and reviews on determinants of utilization are lacking in Ethiopia. OBJECTIVE Synthesize evidence on factors influencing ANC utilization in Ethiopia. METHODOLOGY Relevant articles were searched electronically, filtered and quality assessed. Factors were categorized using a conceptual framework adapted from Anderson’s model and bio-behavioural modelling in health care utilization. RESULTS Twenty-five studies were reviewed. Maternal education, place of residence, family income, husband’s approval, media exposure, pregnancy intention and previous bad obstetric history were the major individual factors affecting ANC utilization. The only health service factor was distance of a health facility. Most of the studies lack standardized outcome measures which could differentiate between non-use verses inadequate use of ANC. Only a single study used conceptual framework. Other important individual factors such as women’s autonomy, cultural beliefs, social networks and health facility factors such as quality, waiting time, and service fee were not examined. No study identified consumer satisfaction as a factor affecting ANC use. CONCLUSIONS AND RECOMMENDATIONS Comprehensive data on factors influencing ANC utilization is lacking in Ethiopia. The measurement of ANC utilization should be standardized and factors should be segregated into those influencing initiation verses adequate use of ANC. Programs intended to improve ANC utilization should focus on women’s education; promote planned pregnancy; target the underprivileged and expand their scope to involve partners in ANC provision. KEY WORDS: antenatal care, prenatal care, utilization, maternal health, factors, systematic review, Ethiopia (Ethiopian Journal of Reproductive Health 2018; 10; 3: 25-37)